The Relationship Between the Duration of Diabetes Mellitus and Diabetic Neuropathy in the Internal Medicine Polyclinic of Linggajati General Hospital - Haris Munandar, Ihsan (PT. Publikasiku Academic Solution, 2024)
Based on data by IDF (International Diabetic Federation), Indonesia has been the 5th country in the world as the biggest diabetes mellitus with the prevalence approximate 9.1 billion people and increasing every year, tha the burden of the country. Diabetic neuropathy is the common complication which presents in diabetic patients, researchers suggest fifty percent of patients with diabetes will get the diabetic neuropathy complication. This study aimed to know the relationship between duration of Diabetes Mellitus Disease and Diabetic Neuropathy also clinical manifestations in Internal Medicine Policlinic Linggajati General Hospital in January to May 2020 period. Sampling technique is consecutive sampling with Inclusion Criteria including identity, gender, age, symptoms and DM duration, statistical test using Chi Square in SPSS 16.0. There is a significant relationship between duration of Diabetes Mellitus and Diabetic Neuropathy (p value = 0.02 ) . There is a relationship between duration of Diabetes Mellitus and Diabetic neuropathy and the clinical features are woman most gender, most age range is 50-60 years old, most DM duration is 5-10 years, and most symptomps is Numbness.